Role of Gut Microbiota Dysbiosis in Breast Cancer and Novel Approaches in Prevention, Diagnosis, and Treatment - (:unkn) unknown (CUREUS INC, 2021)
Breast cancer is the most common cause of cancer-related deaths in women. Breast cancer is still a major cause of morbidity and mortality among women despite all the available diagnostic and treatment modalities. The gut microbiota has drawn keen interest as an additional environmental risk factor in breast cancer, especially in sporadic cases. This article explores factors that disrupt the normal gut microbial composition and the role of gut microbial dysbiosis in the development of breast cancer. We finalized 40 relevant articles after searching Pubmed and Google Scholar using regular keywords and the Medical Subject Headings (MeSH) strategy. Gut microbiota dysbiosis has been shown to play a role in the development of breast cancer via estrogen-dependent mechanisms and non-estrogen-dependent mechanisms involving the production of microbial-derived metabolites, immune regulation, and effects on DNA. The gut microbiota influence estrogen metabolism hence estrogen levels. The metabolites that have demonstrated anticancer properties include lithocholic acid, butyrate, and cadaverine. New approaches targeting the gut microbiota have come up and may yield new advances in the prevention, diagnosis, and treatment of breast cancer. They include the use of prebiotics, probiotics, and hormone supplements to restore normobiosis in the prevention and treatment of breast cancer.
Keywords: oncology; gut microbiota; dysbiosis; estrobolome; breast cancer; intestinal microbiome; RISK; ANTIBIOTICS; ESTROGEN; DIET; EXCRETION; CELL